The Catalytic Role of Superparamagnetic Iron Oxide Nanoparticles as a Support Material for TiO2 and ZnO on Chlorpyrifos Photodegradation in an Aqueous Solution - Wence Herrera; Joelis Vera; Edward Hermosilla; Marcela Diaz; Gonzalo R. Tortella; Roberta Albino Dos Reis; Amedea B. Seabra; María Cristina Diez; Olga Rubilar (Nanomaterials, 2024)
Chlorpyrifos (CP) is a globally used pesticide with acute toxicity. This work studied the photocatalytic degradation of CP using TiO2, ZnO nanoparticles, and nanocomposites of TiO2 and ZnO supported on SPIONs (SPION@SiO2@TiO2 and SPION@SiO2@ZnO). The nanocomposites were synthesized by multi-step incipient wetness impregnation. The effects of the initial pH, catalyst type, and dose were evaluated. The nanocomposites of SPION@SiO2@TiO2 and SPION@SiO2@ZnO showed higher CP photodegradation levels than free nanoparticles, reaching 95.6% and 82.3%, respectively, at pH 7. The findings indicate that iron oxide, as a support material for TiO2 and ZnO, extended absorption edges and delayed the electron–hole recombination of the nanocomposites, improving their photocatalytic efficiency. At the same time, these nanocomposites, especially SPION@SiO2@TiO2, showed efficient degradation of 3,5,6-trichloropyridinol (TCP), one of the final metabolites of CP. The stability and reuse of this nanocomposite were also evaluated, with 74.6% efficiency found after six cycles. Therefore, this nanomaterial represents an eco-friendly, reusable, and effective alternative for the degradation of chlorpyrifos in wastewater treatment.